Differences in financial information and financial status among Malaysian bankrupts - Othman, Mohd Amim; Abdul Rahim @ Abdul Wahab, Husniyah; Sabri, Mohamad Fazli (Australian Academy of Business and Social Sciences, 2015)
Increasing bankruptcy cases among individuals has led to a need for a study done on the bankrupts and their financial affairs. Managing finances well will most probably result in a good financial status. This paper reveals the profile of bankrupts, sources of bankruptcy, types of loans leading to bankruptcy and the financial status of individuals before bankruptcy. A total of 299 bankrupts registered with the Department of Insolvency situated in four big cities in Malaysia responded to self-administered questionnaires distributed by liason officers in those departments. The research shows that the main source of bankruptcy was the inability of individuals to manage their finances well. Other reasons include individuals spending more than their income and failure in business. It was discovered that vehicle loan was found to be the first ranked type of loan leading to their bankruptcy while business loan was ranked second and, personal loan and being a guarantor shared the third rank. Almost half of the individuals in the survey did not attend any financial education prior to their loan approval. Only a quarter of them learnt financial management through their own reading or information from the mass media. The financial status before bankruptcy in general was at an average score. It is therefore suggested that individuals applying for a loan should be equipped with adequate financial education before they are granted the loan. Furthermore, most of the respondents also agreed to the suggestion of attending a financial education program prior to the loan approval. It is hoped that this could be a method to curb individuals from experiencing low financial status after receiving the loan due to financial mismanagement which may result in bankruptcy. The study also suggests that a financial program that would facilitate their bankruptcy release would also be needed.